KONSTRUKSI JARINGAN SOSIAL PESANTREN: STRATEGI EKSIS DI TENGAH PERUBAHAN - Ahmad Salehudin (Religi: Jurnal Studi Agama-agama, 2014)
The perception that kyais are conservative, fanatic, and difficult to be invited in a dialogue will fade away when seeing the fact that their pesantrens are able to survive until today. Kyais are able to maintain pesantrens even though with traditional management, such as less of fundraising support and minimum facilitation. The pesantrens are still exist because they have capability to re- spond any changes and developments of  the world in their own way, which often difficult to be understood from modern logic. This paper explains how pesantrens develop and construct their social network as strateg y to exist in three ways: the transmission of  knowledge, marriage, and structure.